AUTHENTICITY AND VALIDITY OF THE IELTS WRITING TEST AS PREDICTOR OF ACADEMIC PERFORMANCE - Arham Mauriyat (IKIP Siliwangi, 2021)
The International English Language Testing System (IELTS) has become one of the most widely used measurements of English proficiency in the world for academic, professional and migration purposes. For universities in particular, it is expected that applicants’ IELTS scores closely reflect their actual ability in communicating and doing their assignments in English. This study examines the authenticity and predictive validity of the writing section in the IELTS Academic Module by reviewing relevant research on IELTS within the last two decades. In general, those studies have provided evidence that the IELTS writing test suffers from low authenticity and predictive validity, and is thus an inaccurate predictor of a candidate’s performance in writing real-life academic tasks.